The effect of an eight-week training programme on core stability in female junior elite gymnasts - Bassett, S. H.; Leach, L. L. (African Journal for Physical, Health Education, Recreation and Dance, 2011)
A strong core musculature dynamically stabilises the pelvis during functional movements. Although it has been established that focused core training has a positive effect in numerous sports, little is known about the effect in gymnasts. The aim of this study was to assess the effect of an eight week core training programme on the core stability of female junior elite gymnasts.A pre-test post-test, control group design was used in which a core stability test was administered before and after eight weeks. The experimental group (n=7) followed an eight week core stability training programme while the controls (n=15) received no intervention. The core stability test involved the gymnasts holding eight isometric plank positions whilst elevating one leg. The participants were required to hold the position for as long as possible, up to 20 seconds, at which point they were instructed to proceed to the next position. Time for each position was recorded. The training programme consisted of four weeks of static stability training, followed by four weeks of dynamic stability training. Given that the data were "censored" to a maximum of 20 seconds per position, the Kaplan-Meier method was used in the statistical analysis. The results showed that the core stability training group were able to hold five of the eight test positions significantly longer than the controls. This indicates that core stability training enhanced the gymnasts` ability to hold an isometric plank position longer; however it remains to be seen what effect this would have on their gymnastic performance